3mix technique for Root canal failure treatment - Ibrahim Khalil; Shamim Ara Begum; Md Amirul Islam; Md Miftaul Islam; Mohammad Ali Kawsar (Update Dental College, 2017)
Progress has been made in understanding the nature of root canal infection and periapical disease. Sterilization of root canal system is one of the prominent problems. Evidences suggested that Enterococcus faecalis(E.faecalis) caused substantial root canal infections. So, elimination of such organismis important to achieve treatment success. Advance techniques and materials increase the success in Endodontics against Enterococcus faecalis. 3 mix antibiotic therapy a new biologic approach in the treatment of carious lesions. Update Dent. Coll. j: 2016; 6 (2): 27-30